Photosensitivity Reactions Induced by Photochemical Degradation of Drugs - Hajnal Klelemen; Gabriel Hancu; Edina Kacsó; Lajos-Attila Papp (Tabriz University of Medical Sciences, 2022)
Photochemical degradation of drugs can lead to degradation products with potential toxic or allergizing effects for the human body. A significant amount of work has been carried out over the past few decades to clarify the molecular mechanism of photosensitizing processes observed after the administration of certain drugs and exposure to light. There is a close relation between the photosensitizer effect of a drug and its chemical structure. Compounds possessing certain moieties and functional groups in their molecular structure, like aromatic chromophore systems or photo-dissociable bonds that can form free radicals, and consequently are susceptible to have light-induced adverse effects. Photoionization, photodissociation, photoaddition and photoisomerization are the main chemical processes, which can occur during the photochemical decomposition of a pharmaceutical compound. The current study is a short review describing photochemical degradation of certain pharmaceuticals, presenting specific examples from various pharmaceutical classes for the different types of decomposition mechanisms. In vivo methods and clinical tests available for the investigation of photosensitizing reactions are also discussed.